Lactose Intolerance: What Consumers Need to Know - Matt Krug; Amarat Simonne (EDIS)
Lactose intolerance is a condition that occurs when people cannot effectively digest lactose. Lactose intolerance is often related to our age and genetic origin and the majority of the world’s population with Asian or African origins is lactose intolerant.Managing lactose intolerance and malabsorption depends on the intensity and severity of symptoms. Treatments include reducing or eliminating lactose-containing foods (dairy), replacing lactose-containing foods with other foods containing similar nutrients, and using lactase supplements or similar products.  This publication will provide information and guidance for consumers so that they may find the right information for their situation.